2019
DOI: 10.1002/jbm4.10196
|View full text |Cite
|
Sign up to set email alerts
|

Local Tumor Recurrence and Escape from Suppression of Bone Resorption With Denosumab Treatment in Two Adolescents With Giant Cell Tumors of Bone

Abstract: Giant cell tumors of bone (GCTB) may be difficult to resect because of size or location. We describe two adolescents who were treated with denosumab and followed for tumoral and biochemical responses. Denosumab was effective in achieving sufficient regression to allow surgical resection and in preserving peritumor cortical bone. Reactivation of bone resorption markers was noted while the patients were receiving monthly denosumab. One patient suffered a local tumor recurrence. Denosumab was safe in enabling sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…Observed side effects were similar as previously described, including hypocalcemia during treatment and rebound hypercalcemia with discontinuation (17,(20)(21)(22)(23)(24)(25)(26)(27). Namely, three of the four patients experienced hypocalcemia with the initiation of denosumab, noted within 1 week after medication administration, which was corrected with calcium supplementation.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Observed side effects were similar as previously described, including hypocalcemia during treatment and rebound hypercalcemia with discontinuation (17,(20)(21)(22)(23)(24)(25)(26)(27). Namely, three of the four patients experienced hypocalcemia with the initiation of denosumab, noted within 1 week after medication administration, which was corrected with calcium supplementation.…”
Section: Discussionsupporting
confidence: 80%
“…Given the unknown and unstudied effects of denosumab on growing bones, the use of denosumab in children has been limited. To date, we have found reports of 17 children and adolescents in the literature who have been treated with denosumab for various indications, including osteogenesis imperfecta type VI (20), juvenile Paget's disease (21), giant cell tumors (22)(23)(24)(25)(26), fibrous dysplasia (27), osteoglyphonic dysplasia (28), cherubism (17), and non-syndromic giant cell lesions of the jaw (17,26). The use of denosumab in NL/MGCL has been reported in one adult (17).…”
Section: Discussionmentioning
confidence: 99%
“…A critical review of these published studies identified 60 studies that met the inclusion criteria for the present meta-analysis ( Table 1 ). 11 , 12 , 44 , 60 - 116 The www.clinicaltrials.gov website showed 7 ongoing studies of denosumab in the treatment of GCTB. The majority of the studies examined for this meta-analysis were case reports, case series studies, and nonrandomized, uncontrolled, open-label phase II studies ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…14 Several studies have reported denosumab to be an effective treatment option for aggressive and difficult cases of GCTB. 15 20 However, despite the reported benefits, adjuvant treatment using denosumab has recently been shown to be associated with a risk of recurrence in curettage treatment of GCTB. 12,21 A phase 3 trial of adjuvant treatment using denosumab in surgical settings has been running in Japan since 2017; however, the study is still ongoing due to difficulty of collecting entries.…”
Section: Brief Introductionmentioning
confidence: 99%